Faktor-faktor yang Berhubungan dengan Kepuasan Pasien di Instalasi Rawat Jalan RSUP Prof. Dr. R. D. Kandou, Manado - Pontoh J. Ch. Putera; Jimmy Posangi; Aaltje E. Manampiring (Universitas Sam Ratulangi, 2023)
Abstract: Measuring the level of patient satisfaction in hospitals must be carried out periodically, accurately, and continuously. Patient satisfaction can be achieved if the patient receives services according to what is needed and expected. The level of patient satisfaction describes the quality of services provided by the hospital. This study aimed to analyze factors related to outpatient satisfaction at Prof. Dr. R. D. Kandou Hospital, Manado. This was a quantitative study with a cross sectional approach. This study was conducted at Prof. Dr. R. D. Kandou Hospital with a total sample of 390 patients taken by simple random sampling. Data were obtained from questionnaires and were analyzed univariately, bivariately using the chi-square test, and multivariately using the logistic regression test. Statistical calculation using the SPSS program. The results of the chi-square test showed the p-values of relationships between patient satisfaction and the variable aspects, as follows: tangibles p=0.000; responsiveness p=0.000; reliability p=0.000; assurance p=0.000; and empathy p=0.000. The results of multivariate analysis using the logistic regression test obtained that the highest Exp (B) value of 586.267 on the tangibles aspect. In conclusion, tangibles, responsiveness, reliability, assurance and empathy have significant relationships with patient satisfaction to the services at Prof. Dr. R. D. Kandou Manado. The most related factor with patient satisfaction is tangibles. Keywords: patient satisfaction; service quality; tangibles; responsiveness; reliability; assurance; empathy Abstrak: Pengukuran tingkat kepuasan pasien di rumah sakit wajib dilakukan seara berkala, akurat dan berkesinambungan. Kepuasan pasien dapat tercapai apabila pasien menerima pelayanan sesuai dengan yang dibutuhkan dan diharapkan. Tingkat kepuasan pasien menggambarkan kualitas pelayanan yang diberikan oleh rumah sakit. Penelitian ini bertujuan untuk menganalisis faktor yang berhubungan dengan kepuasan pasien rawat jalan di RSUP Prof. R. D. Kandou Manado. Jenis penelitian ialah kuantitatif dengan desain potong lintang. Penelitian ini dilaksanakan di RSUP Prof. R. D. Kandou Manado dengan jumlah sampel 390 pasien yang diambil secara simple random sampling. Data diperoleh melalui kuesioner, kemudian dianalisis secara univariat, bivariat dengan menggunakan uji chi square, dan multivariat menggnakan uji regresi logistik. Penghitungan statistik menggunakan program SPSS. Hasil uji chi-square terhadap hubungan dengan kepuasan pasien mendapatkan untuk aspek tangibles p=0,000; responsiveness p=0,000; reliability p=0,000; assurance p=0,000; dan empathy p=0,000. Hasil analisis multivariat menggunakan uji regresi logistik mendapatkan nilai Exp (B) tertinggi yaitu 586,267 pada aspek tangibles. Simpulan penelitian ini ialah tangibles, responsiveness, reliability, assurance, dan empathy berhubungan bermakna dengan kepuasan pasien terhadap pelayanan di RSUP Prof. R. D. Kandou Manado. Faktor yang paling berhubungan dengan kepuasan pasien yaitu tangibles. Kata kunci: kepuasan pasien; kualitas layanan; tangibles; responsiveness; reliability; assurance; empathy